Characterization of Natural Face Toner from Rice-washed Water - Tantra Diwa Larasati; Novy Pralisa Putri; Helda Niawanti; Linda Eka Pratiwi; Delthania Ekaristi Paulina Gedoan (Jurnal Sains dan Terapan Kimia, 2022)
Toner is a skin treatment that serves to refresh and clean facial skin. This study used rice-washed water as the main ingredient for producing toner. Rice-washed water is the main ingredient because it contains abundant nutrients such as carbohydrates in the form of starch, fat, protein, gluten, cellulose, hemicellulose, sugar, vitamins, and minerals. This study aims to determine the effect of toner application made from rice-washed water on the skin, storage time on toner quality, and the production process. The method used in this study uses a simple method of soaking with a rice/water with a various ratio (kg/L). The analysis results show that the toner has a pH of 6.4, considered safe for all skin types with good moisture. The effect on skin moisture was analyzed on six respondents. The toner has a viscosity that is not too thick with a cloudy white color caused by rice grains. Rice grains are beneficial for the skin because they can regenerate skin cells. Rice-washed water toner for seven days contains fat, manganese, protein, oil, fat, and is odorless.